ANTIOXIDANT ACTIVITY OF 2,6,4’-TRIHYDROXY-4-METHOXY BENZOPHENONE FROM ETHYL ACETATE EXTRACT OF LEAVES OF MAHKOTA DEWA (Phaleria macrocarpa (Scheff.) Boerl.) - Susilawati Susilawati; Sabirin Matsjeh; Harno Dwi Pranowo; Chairil Anwar (Universitas Gadjah Mada, 2011)
Mahkota dewa plant (Phaleria macrocarpa (Scheff.) Boerl.) which is included into family of Thymelaeaceae is one of Indonesia's traditional medicines. Chemical constituent has been isolated from ethyl acetate extract of leaves of mahkota dewa. Sample was extracted with methanol, concentrated then extracted by n-hexane, chloroform and ethyl acetate. The ethyl acetate extract was separated and fractionated by column chromatography. The first fraction was purified by TLC preparative and recrystalization. Compound was isolated as red-brown spherical crystal in 8 mg (m.p. 129-131 °C). Its spot gave dark fluoroscence at TLC plate (UV366) with Rf of 0.3 at TLC chromatogram with eluent of n-hexane : ethyl acetate (7:3); 0.6 with n-hexane : ethyl acetate (1:1); 0.9 with -hexane : ethyl acetate (4:6). This compound was dissolved in methanol. Compound was identified by UV, IR, 1H NMR, 13C NMR and NMR 2 dimension (HMQC, COSY, HMBC and DEPT-135) spectroscopic as 2,6,4'-trihydroxy-4-methoxybenzophenon. This compound as well as the ethyl acetate extract showed antioxidant activity on DPPH with IC50 was 10.57 and 101.06 μg/mL, respectively. This compound showed strong antioxidant activity on DPPH, almost to the standard antioxidant activity of quercetin (IC50 of 2.93 μg/mL)